Correlation of in vivo and ex vivo1H-MRI with histology in two severities of mouse spinal cord injury - Noristani, Harun N.; Lonjon, Nicolas; Cardoso, Maïda; Le Corre, Marine; Chan-Seng, Emilie; Captier, Guillaume; Privat, Alain; Coillot, Christophe; Goze-Bac, Christophe; Perrin, Florence E. (Frontiers in Neuroanatomy, 2015)
Spinal cord injury (SCI) is a debilitating neuropathology with no effective treatment. Magnetic resonance imaging (MRI) technology is the only method used to assess the impact of an injury on the structure and function of the human spinal cord. Moreover, in pre-clinical SCI research, MRI is a non-invasive method with great translational potential since it provides relevant longitudinal assessment of anatomical and structural alterations induced by an injury. It is only recently that MRI techniques have been effectively used for the follow-up of SCI in rodents. However, the vast majority of these studies have been carried out on rats and when conducted in mice, the contusion injury model was predominantly chosen. Due to the remarkable potential of transgenic mice for studying the pathophysiology of SCI, we examined the use of both in and ex vivo 1H-MRI (9.4 T) in two severities of the mouse spinal cord injury (hemisection and over-hemisection) and documented their correlation with histological assessments. We demonstrated that a clear distinction between the two injury severities is possible using in and ex vivo 1H-MRI and that ex vivo MR images closely correlate with histology. Moreover, tissue modifications at a remote location from the lesion epicentre were identified by conventional ex vivo MRI analysis. Therefore, in vivo MRI has the potential to accurately identify in mice the progression of tissue alterations induced by SCI and is successfully implemented by ex vivo MRI examination. This combination of in and ex vivo MRI follow-up associated with histopathological assessment provides a valuable approach for further studies intended to evaluate therapeutic strategies on SCI.